Metagenomic Reveals the Role of Autochthonous Debaryomyces hansenii in the Fermentation and Flavor Formation of Dry Sausage - Qian Chen; Siyuan He; Mengtong Li; Yumeng Sui; Baohua Kong; Rongxin Wen (Foods)
The effect of Debaryomyces hansenii SH4, a typical aroma enhancer, on flavor formation of the dry fermented sausage was investigated using gas chromatography-mass spectrometry and metagenomic sequencing. The results showed that inoculation with D. hansenii SH4 promoted volatile compound formation from carbohydrate and amino acid metabolism and accelerated ester synthesis. The enzymes, genes, and microorganisms involved in the formation pathway of volatile compounds based on microbial metabolism were predicted and constructed into a metabolic pathway network. D. hansenii, Lactobacillus curvatus, Lactobacillus sakei, Lactobacillus plantarum, Leuconostoc fallax, Weissella minor, and Staphylococcus and Candida species were found to be the predominant functional microbes for flavor development in dry sausage. This study established a new insight into the metagenome-based bioinformatic effects of D. hansenii SH4 as a starter culture on the microbial synthesis of key volatile compounds in dry sausage.